2018
DOI: 10.1016/j.ymthe.2018.01.023
|View full text |Cite
|
Sign up to set email alerts
|

miR-296-3p Negatively Regulated by Nicotine Stimulates Cytoplasmic Translocation of c-Myc via MK2 to Suppress Chemotherapy Resistance

Abstract: This study aimed to identify mechanisms by which microRNA 296-3p (miR-296-3p) functions as a tumor suppressor to restrain nasopharyngeal carcinoma (NPC) cell growth, metastasis, and chemoresistance. Mechanistic studies revealed that miR-296-3p negatively regulated by nicotine directly targets the oncogenic protein mitogen-activated protein kinase-activated protein kinase-2 (Mapkapk2) (MK2). Suppression of MK2 downregulated Ras/Braf/Erk/Mek/c-Myc and phosphoinositide-3-kinase (PI3K)/Akt/c-Myc signaling and prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 57 publications
(66 reference statements)
1
39
1
Order By: Relevance
“…in the present study, the expression of key proteins of Pi3K/aKT, ras and Wnt signaling was determined following the downregulation of mir-296-3p in GBM. The downregulation of Wnt signaling was only observed in GBM cells (43,44), but the observation excluded the previously reported regulatory association between mir-296-3p and c-Myc. The results of the present study indicated that mir-296-3p promoted c-Myc expression via activating the Wnt signaling.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…in the present study, the expression of key proteins of Pi3K/aKT, ras and Wnt signaling was determined following the downregulation of mir-296-3p in GBM. The downregulation of Wnt signaling was only observed in GBM cells (43,44), but the observation excluded the previously reported regulatory association between mir-296-3p and c-Myc. The results of the present study indicated that mir-296-3p promoted c-Myc expression via activating the Wnt signaling.…”
Section: Discussioncontrasting
confidence: 68%
“…been suggested to target MK2 and PrKca in nasopharyngeal carcinoma and lung adenocarcinoma, respectively (43,44). The downregulation of MaPK activated protein kinase 2 and protein kinase cα was observed to inhibit Pi3K/aKT and ras signaling, resulting in the downregulation of c-Myc (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that expression of VPS33B was significantly reduced in DSS/AOM‐induced mice CRC models. Furthermore, we also observed that VPS33B was suppressed by nicotine, a key component of tobacco, which is known as a carcinogen and closely associated with cancers including CRC via RAS/ERK/c‐Jun‐induced transcription suppression of VPS33B promoter in human CRC cells. These data suggest that VPS33B can be damaged by chemical carcinogens and participates in CRC pathogenesis.…”
Section: Discussionmentioning
confidence: 62%
“…Consistent with our results, underexpression of miR-296 may cause tumor progression by inducing EMT events in some tumor cells [33,34]. miR-296 negatively regulated by nicotine directly targets mitogen-activated protein kinase-activated protein kinase-2-induced Ras/Braf/Erk/Mek/c-Myc or Phosphoinositide 3-kinase (PI3K)/Protein Kinase B(AKT)/c-Myc signaling to stimulate its own expression and suppress NPC cell proliferation and metastasis [35].…”
Section: Discussionmentioning
confidence: 85%